Композит кубічного нітриду бору, модифікований диборидом титану - Гарбуз, Т.О.; Беженар, М.П.; Божко, С.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The studying of composites obtained by a sintering at high pressure of a mixture cBN + TiB₂ + 10 % Al, and the test of the cutting plates made from them have shown, that the structure with high strength of phase boundaries and the high wear-resistence is obtained at the complete participation of a titanium diboride in reactionary interacting that is attained at the content in a mixture 5-10 % TiB₂.